Regional Diversification of Rural Territories with Limited Spatial Location of Green Tourism Objects - Kyrylov, Yurii Y.; Hranovska, Viktoriia H.; Kolokolchykova, Iryna V.; Sakun, Alina G.; Nikitenko, Kateryna S.; Katsemir, Yana V. (Journal of Environmental Accounting and Management, 2026)
The relevance of research is that the process of diversification of rural entrepreneurship has its own specific conditions and features. The aim of paper is to substantiate methodological approaches to the assessment and forecasting of regional diversification of rural areas with limited spatial location of green tourism objects. Article deals with the process of regional diversification of rural territories with limited spatial placement of green tourism objects. It is proved that entrepreneurship in field of green tourism is a specific type of tourism activity, has a social, environmental and economic impact on the development of rural territories of the region.